Design of electrocatalysts with reduced Pt content supported on mesoporous NiWO4 and NiWO4-graphene nanoplatelets composite for oxygen reduction and hydrogen oxidation in acidic medium. (22nd February 2023) - Somacescu, Simona; Osiceanu, Petre; Calderon Moreno, Jose Maria; Culita, Daniela C.; Neațu, Florentina; Trandafir, Mihaela M.; Neațu, Ștefan; Kuncser, Andrei; Szijjártó, Gábor P.; Tálas, Emília; Tompos, András; Borbáth, Irina; et al.
Abstract: Herein, a new direct synthesis route leading to a mesoporous NiWO4 with crystalline framework and NiWO4 - graphene nanoplatelets (GNP) composite is reported. Ni and W assembled into a mesoporous tungstate type of symmetry by co-precipitation synthesis route and its composite with GNP were used as supports for electrocatalysts, with reduced Pt content (8 wt.%), in oxygen reduction reaction (ORR) and hydrogen oxidation reaction (HOR) in acidic medium. A comprehensive assessment of the modifications related to the crystalline and porous structures, morphological aspects as well as the surface chemistry aiming to explain the electrochemical properties was performed. It was found that the presence of GNP during the synthesis process leads, mainly, to the enhanced growth of NiWO4 nanocrystallites, as well as induces changes in the surface chemistry. The electrochemical results show that the introduction of GNPs into the NiWO4 composite support leads to a significant improvement in the activity of the Pt electrocatalyst in ORR and HOR compared to both initial NiWO4 and Pt/NiWO4 samples, as well as mechanical mixtures of these catalysts with carbon. Mass activity for hydrogen oxidation, determined in a mixed kinetic-diffusion controlled region, obtained on the 8 wt.% Pt/NiWO4 -GNP catalyst was significantly higher compared to the commercial 20 wt.% Pt/C Quintech catalyst. Our comprehensive structural and surface chemistry assessments indicate this composite material as a viable electrocatalyst for PEMFCs using a broader type of fuels. Highlights: Mesoporous NiWO4 and NiWO4 -GNP composite supports. The addition of GNP to mesoporous NiWO4 increases conductivity. The presence of GNP determines the formation of different Ni and W chemical species. Improved performance of Pt/NiWO4 -GNP compared to Pt/NiWO4 -BP and NiWO4 -BP materials. Enhanced HOR activity of GNP–containing NiWO4 –based Pt electrocatalysts.